2022
DOI: 10.1038/s41598-022-06370-w
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy study of suspected primary ciliary dyskinesia patients

Abstract: Primary ciliary dyskinesia (PCD) is a rare autosomal recessive condition often presenting with chronic respiratory infections in early life. Transmission electron microscopy (TEM) is used to detect ciliary ultrastructural defects. In this study, we aimed to assess ciliary ultrastructural defects using quantitative methods on TEM to identify its diagnostic role in confirming PCD. Nasal samples of 67 patients, including 37 females and 30 males (20.3 ± 10.7 years old), with suspected PCD symptoms were examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(44 reference statements)
1
3
1
Order By: Relevance
“…Regarding TEM findings, in contrast to the current study that showed ODA loss and MTD + IDA loss to be equally the most common hallmark defects, ODA + IDA loss was the most common hallmark defect reported in previous studies in the Kingdom of Saudi Arabia (KSA), Oman, and Iran 32–34 . ODA absence as a Class 1 hallmark defect was not reported among the Iranian cohort 34 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding TEM findings, in contrast to the current study that showed ODA loss and MTD + IDA loss to be equally the most common hallmark defects, ODA + IDA loss was the most common hallmark defect reported in previous studies in the Kingdom of Saudi Arabia (KSA), Oman, and Iran 32–34 . ODA absence as a Class 1 hallmark defect was not reported among the Iranian cohort 34 …”
Section: Discussioncontrasting
confidence: 99%
“…[32][33][34] ODA absence as a Class 1 hallmark defect was not reported among the Iranian cohort. 34 Class 2 defects affected 5/34 (14.70%) of the adequate samples.…”
Section: Discussionmentioning
confidence: 83%
“…Although the lack of any other PCD diagnostic test limited the direct comparisons that could be made between individual clinical diagnoses and the corresponding TEM observations, clinical suspicion of PCD and ciliary ultrastructure overall appeared concordant in 43% of the cases. This value compares well with other recent PCD-TEM-only reports from resource-limited settings, for example 17.9% in an Iranian study ( 23 ), 34% in the Palestinian cohort ( 11 ) and 43% (all cases) −70% (only cases with high clinical suspicion) in a Brazilian study ( 6 ). These studies were based on large numbers of clinically suspected PCD cases of all age groups, in contrast to the current small pediatric study in which correlation between clinical and ultrastructural data was probably due to the pediatric pulmonologists' heightened awareness of PCD as part of a diagnostic differential, to the small sample size, and to the lack of any other test to corroborate the clinical - TEM findings.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, EM has been used to further investigate the detailed structures of cell organelles to validate potential novel findings discovered through research studies. For example, EM has been used to: a) assess ciliary ultrastructural defects in ciliary disorders 13 ; b) identify stored material in lysosomal storage disorders, including neuronal ceroid lipofuscinoses and Batten disease 14 ; and c) isolate highly infectious and contagious microorganisms, primarily viruses, to enable production of vaccines in microbial diseases, e.g. SARS-CoV-2/coronavirus.…”
Section: Discussionmentioning
confidence: 99%